Framing Freedom of Religion or Belief for Countering Violent Extremism in Kenya: The Equivalency Framework of the Evangelical Alliance of Kenya - Maseno-Ouma, Loreen (The review of faith & international affairs, 2018)
Over the past years, and in the aftermath of terror attacks, religious organizations in Kenya have issued press statements which conflate discourses on war against terror, security, and freedoms of religion. Using the example of one umbrella religious organization, the Evangelical Alliance of Kenya (EAK), this paper demonstrates how freedom of belief is framed in contexts of terror violence. Using framing theory and specifically the equivalency approach, EAK as a frame sponsor presents an alternative interpretive scheme on religious freedoms for judgements relating to terror attacks and related violence.